Utilising Lapindo Sidoarjo Mud and Mount Merapi Yogyakarta Ash as Alternative Materials for Earthenware and Stoneware Manufacture - Kasiyan,; B Muria Zuhdi, (Wacana Seni Journal of Arts Discourse, 2019)
The explosion of hot mud in Sidoarjo, East Java Indonesia in 2006 was a human catastrophe that has had devastating social, environmental, economic and health consequences. This article presents a fresh perspective on how some benefit might be derived from this disaster. It reports the results of a study that aimed to assess the feasibility of using a combination of Lapindo Sidoarjo mud (LSM) and Mount Merapi Yogyakarta ash (MMYA) as raw materials in the manufacture of earthenware and stoneware ceramic products. The project's methodology was adapted from the four-step Research Development Model (e.g., define, plan, develop and validate). The results showed that a combination of 60% LSM and 40% MMYA can be used to make earthenware ceramics and a 50:50 mix can be used to make stoneware ceramics. The ceramics were successfully tested using the techniques of throwing, moulding and handbuilding.